PENGARUH AIR JAHE TERHADAP PENURUNAN GULA DARAH - Yuli Astuti (Yayasan Pendidikan Medika Indonesia, 2022)
Diabetes Mellitus is a metabolic disease characterized by increased levels of glucose in the blood caused by impaired body function in regulating glucose metabolism. This study aims to determine the effect of ginger boiled water in lowering blood glucose in patients with diabetes mellitus. The research design used Pre-Experiment One group Pre-test and Post-Test with Purposive Sampling method as many as 6 respondents, carried out in the Cililitan village, East Jakarta, 2021. The research variable is the dependent variable of blood sugar levels, and the independent is ginger boiled water. Data analysis using Paired t Test. The results showed that the average glucose level of the respondents before the intervention was 287.7 mg/dl, after the intervention was 244.7 mg/dl, with an average decrease of 63 mg/dl. There is an effect of ginger boiled water on decreasing blood sugar levels with a value of -value = 0.002 the mean is positive (36). The decrease was due to an increase in metabolism caused by the phenolic active substances in ginger. Drinking ginger boiled water can be implemented to reduce blood sugar levels in patients with diabetes mellitus.